Effects of an educational intervention on the technical writing competence of engineering students (2016)
This article presents the design, implementation and appraisal of an educational intervention developed to explore how education, practice and feedback of cognitive elements, regarding writing summaries, have an effect on the technical writing competence of freshman engineering students. The educational intervention was designed based on the methodol-ogy of Writing Across the Curriculum (WAC) and it consisted of three phases: teaching, practice and feedback. In total, 177 students participated, distributed into three groups: 54 Electronic Engineering students (year 2014), 57 Electrical Engineering students (year 2015) and 66 Electronic Engineering students (year 2015). The intervention effects were studied by quantitative and qualitative evidence. Quantitative evidence was collected through an evaluation rubric of the summaries written by the students; this rubric analyzes ten criteria of the writing competence. Qualitative evidence was collected through open-ended questions about the students’ learning experience throughout the intervention. Results show that the three partici-pating groups improved their technical writing competence due to their participation in this educational intervention. Sen-tence construction (g-Hedges = 0,62) and text sequences (g-Hedges = 0,59) criterion presented the highest effect rates. The other writing criteria, evaluated through the rubric, presented a positive gain with statistical significance, but only in some groups of students.